Angiotensin-(1-7) blocks the angiotensin II-stimulated superoxide production - Polizio, Ariel Héctor (2007)
Angiotensin (Ang)-(1–7), a bioactive compound of the renin–angiotensin system, exerts effects leading to blood pressure reduction which counterbalance Ang II pressor actions. The present study was conducted to examine Ang-(1–7) and Ang II effects on superoxide anion production in rat aorta using the lucigenin chemiluminescence method. Ang II dose-dependently increased superoxide anion formation when compared tocontrol levels; a maximal increase (2.5-fold) was observed with 1×10−10M peptide concentration. The Ang II-stimulated superoxide formation was blocked by 1×10−10M losartan, the specific AT1 receptor antagonist, but not by 1×10−10M PD 123319, the AT2 receptor antagonist, suggesting that the increased superoxide levels caused by Ang II are mediated through AT1 receptors activation. The Ang II-stimulated superoxideproductionwas not modified by 2×10−8Mallopurinol or 1×10−7Mindomethacin, but was completely abolished byNAD(P)H oxidase inhibitors: 1×10−8M diphenylene iodonium, or 2×10−8M apocynin, demonstrating that NAD(P)H oxidase participates in such response.In contrast to Ang II, Ang-(1–7) concentrations ranging 1×10−12 to 1×10−6M did not modify superoxide anion levels, but prevented the Ang II-enhanced superoxide production. In conclusion, we demonstrated that Ang-(1–7) blocks the pro-oxidant effects of Ang II, thus reducing the superoxide anion production and delaying the hypertension development.